EMPOWERMENT OF URBAN FARM WOMEN IN SUPPORTING THE IMPROVEMENT OF THE FAMILY ECONOMY WITH LAND USE OF YARDS: PEMBERDAYAAN WANITA TANI KOTA DALAM MENDUKUNG PERBAIKAN EKONOMI KELUARGA DENGAN PEMANFAATAN LAHAN PEKARANGAN - Indarwati Indarwati; Dwie Retna S; Jajuk Herawati; Tatuk Tojibatus S (Yayasan Education and Social Center, 2021)
Peasant Women Kota has the potential as a driving force for urban community empowerment. The position of women who have been in the kingdom with men has a considerable share in supporting economic improvement. The reluctance of urban peasant women in productive activities is caused, among others, by a lack of knowledge to work, a lack of motivation to move in productive economic activities, and the lack of introduction of The Application of Some Appropriate Technology that they can actually do. There are many productive economic activities that can be done; To fill your free time while taking care of the household. Productivity of the concentration of yard land / land around the place of residence is often forgotten. The productivity of yard land use is one solution. The purpose of the activity is